The Effects of Inpatients’ Privacy on Satisfaction (Journal of Pharmaceutical Negative Results, 2022)
Purpose: This study investigates the effects of inpatients’ privacy on their satisfaction in a training and research hospital.Methods: This cross-sectional study was designed as quantitative research using a survey method. The questionnaire was administered to 222 participants ((F=114, M=108) in a training and research hospital in Istanbul using convenience sampling. The questionnaire consisted of three parts: a socio-demographic form, the Inpatient Satisfaction Questionnaire (ISQ), and the Patient Privacy Inventory (PPI). Confirmatory factor analyses and measurement models were applied to the Inpatient Satisfaction Questionnaire and the Patient Privacy Inventory. Cronbach’s Alpha, Mean Average Variance Extracted (AVE), Composite Reliability (CR) values, reliability, convergent and discriminant validity analyzes were performed before model testing. The research model examined the analysis using latent variables for the PPI scale sub-dimensions and the ISQ sub-dimensions.Results: The care given to patient privacy explains patient satisfaction at a rate of 50%. The respect for patients’ physical confidentiality, the knowledge about patients’ privacy, and patients’ medical confidentiality accounted for 48.65% of the physical environment, 55.43% of the physician-patient relationship, 45.55% of the patient care, and 56.38% of hospitalization and treatment process subdimensions.Conclusions: The current study examines inpatients in a training and research hospital in Istanbul, bringing us to the conclusion that taking care of patient privacy leads to patient satisfaction. Paying attention to the patients’ privacy influences patient satisfaction as high as 50%.